Inclusion Module as a Guide for Disability Service Units (ULD) in Assisting Students with Disabilities - Dedi Nasruddin; Syarvia (Universitas Pendidikan Ganesha, 2026)
The university has accepted students with disabilities, but does not yet have standard guidelines for implementing mentoring, resulting in partial and undirected inclusive services. This study aims to develop an inclusion module as an operational guideline for the ULD to ensure mentoring for students with disabilities is carried out systematically, professionally, and sustainably. This study uses the Research and Development (R&D) method with the ADDIE model, which consists of the stages of needs analysis, design, development, implementation, and evaluation. The research subjects comprised five experts who served as validators, assessing content, language, presentation, and graphics using a five-point Likert scale. The analysis technique used quantitative and qualitative analysis. The validation results showed that all aspects received a high category, with a percentage of 82–90%, indicating that this module is valid, practical, and feasible to implement in the context of higher education. These findings indicate that the Inclusion Module is a worthy reference for implementing mentoring for students with disabilities. In addition to strengthening the university's commitment to providing inclusive higher education, the implementation of this module also has strategic implications for supporting the achievement of sustainable development goals, particularly in the areas of quality education, equality, and fair learning opportunities for all students without discrimination.